Transformational Leadership and Retention of Young Health Workers: The Mediating Role of Job Satisfaction and Well-Being - Rian, Dafid; W, Wahidin (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Retaining young health workers is a major challenge in the healthcare system, especially in the post-pandemic era. Transformational leadership is seen as one of the strategic approaches that has the potential to increase employee loyalty and well-being, but the mechanisms of its influence on retention intentions are not yet fully understood, particularly through psychological roles such as job satisfaction and well-being. This study aims to analyze the influence of transformational leadership on the retention of young healthcare workers and to test the mediating role of job satisfaction and well-being in this relationship. Method: The study employs a quantitative approach with an explanatory design. Data were collected from 132 young healthcare workers in Central Java via a closed-ended questionnaire. The instruments were adapted from the MLQ scale, Spector, WHO-5, and Tremblay. Path analysis was conducted to test direct and indirect relationships between variables, and the Sobel test was used to verify mediation. Result: The results indicate that transformational leadership significantly influences job satisfaction (β=0.451; p<0.001) and well-being (β=0.417; p<0.001), both of which also significantly influence retention. Leadership also has a direct effect on retention (β=0.178; p=0.041), indicating partial mediation. The Sobel test shows that job satisfaction and well-being are significant mediators. Conclusion: Transformational leadership plays a crucial role in shaping young healthcare workers' decisions to stay, through the creation of positive job satisfaction and psychological well-being. Managerial strategies that integrate humanistic leadership approaches and psychosocial interventions are deemed essential for building a sustainable work system.